2011
DOI: 10.1371/journal.pone.0024112
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Salmonella Infection Mechanisms in Plants and Animals

Abstract: Salmonella virulence in animals depends on effectors injected by Type III Secretion Systems (T3SSs). In this report we demonstrate that Salmonella mutants that are unable to deliver effectors are also compromised in infection of Arabidopsis thaliana plants. Transcriptome analysis revealed that in contrast to wild type bacteria, T3SS mutants of Salmonella are compromised in suppressing highly conserved Arabidopsis genes that play a prominent role during Salmonella infection of animals. We also found that Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(171 citation statements)
references
References 51 publications
10
157
1
1
Order By: Relevance
“…have been previously reported in 16S rRNA surveys of root nodules of wild legumes 32,33 . There is mounting evidence that human-pathogenic enteric bacteria such as Salmonella can colonize plant tissues, and use similar mechanisms for infection of animal and plant hosts 34,35 . Our findings (and additional examples discussed in Supplementary Note) serve to further underscore the impact of broadening the phylogenomic R e s o u R c e representation of public databases, in this case, in adding to complementary cultivation-independent efforts to explore the breadth of microbial diversity and ecology.…”
Section: Improved Taxonomic Assignment Of Metagenomic Sequencesmentioning
confidence: 99%
“…have been previously reported in 16S rRNA surveys of root nodules of wild legumes 32,33 . There is mounting evidence that human-pathogenic enteric bacteria such as Salmonella can colonize plant tissues, and use similar mechanisms for infection of animal and plant hosts 34,35 . Our findings (and additional examples discussed in Supplementary Note) serve to further underscore the impact of broadening the phylogenomic R e s o u R c e representation of public databases, in this case, in adding to complementary cultivation-independent efforts to explore the breadth of microbial diversity and ecology.…”
Section: Improved Taxonomic Assignment Of Metagenomic Sequencesmentioning
confidence: 99%
“…These mutants also induced more apparent symptoms in Arabidopsis plants, suggesting that, in this case, T3SSs are necessary to prevent the hypersensitive response. In fact, transcriptomic analysis indicated that 649 host genes are induced specifically by the T3SS1 mutant, and many of these genes encode proteins related to responses against pathogens [170]. Consistent with this idea, wild-type bacteria, but not a T3SS1 mutant, were able to suppress the oxidative burst and the increase in extracellular pH after inoculation of a tobacco cell culture [171].…”
Section: Salmonella In Plantsmentioning
confidence: 80%
“…Interestingly, components of Salmonella T3SS1 also appear to be recognized by plants, since mutants lacking this system (spaS or sipB mutants) exhibit increased colonization of alfalfa roots and wheat seedlings [169]. These results contrast with the reduced proliferation observed for mutants prgH and ssaV, lacking T3SS1 and T3SS2, respectively, in Arabidopsis thaliana [170]. These mutants also induced more apparent symptoms in Arabidopsis plants, suggesting that, in this case, T3SSs are necessary to prevent the hypersensitive response.…”
Section: Salmonella In Plantsmentioning
confidence: 99%
“…Even though some studies demonstrated that Salmonella involves its virulence genes in the interactions with plants, and that under some conditions it can elicit disease-like signs in plants (Schikora et al, 2011), it is not commonly considered a phytopathogen (Barak and Schroeder, 2012). Therefore, for the purpose of this article, we broadly define "susceptibility" of tomatoes as being conducive to proliferation of Salmonella following an infection into a shallow wound in the fruit epidermis.…”
Section: Resultsmentioning
confidence: 99%